Investigation of common mode voltages of single stage boost inverter for five phase induction motor drive - Yaramasu Suri Babu; Koritala Chandra Sekhar (Institute of Advanced Engineering and Science, 2022)
In this manuscript, the single stage boost inverter is proposed to eliminate the common-mode voltage (CMV) and electromagnetic interference (EMI) in the motor drives. The proposed topology has the capability of eliminating the effects of intrinsic CMV without any additional filters, active or passive elements, and modified pulse width modulated (PWM) techniques. This topology is proposed with the rearrangement of filter components from ac side to mid place in such a way that the capacitor constantly clamped to the DC bus, and the inductor is placed at the mid-point of half-bridge module and supply to achieve the high gain. This arrangement is also eliminating the effect of switching natured common-mode voltage, which generally occurs in any conventional PWM inverter. Conventional PWM techniques can be implemented to this topology without any modification in the control strategy. The proposed topology is simulated in a MATLAB Simulink to verify the operation and CM reduction capabilities with the results of experimental prototype. In the manuscript, the proposed topology is compared with the traditional inverters and modulation schemes in terms of the CMV effect elimination to explain its effectiveness.